A Role of Artificial Intelligence in the Context of Economy: Bibliometric Analysis and Systematic Literature Review - Jrad, Majida (International Journal of Membrane Science and Technology, 2023)
This bibliometric analysis aims to explore and assess the multifaceted impact of technology on the economy through a comprehensive review of academic literature. By systematically examining a wide range of research articles, this study intends to provide insights into the various ways in which technology influences economic growth, productivity, innovation, and other key indicators. The analysis will identify trends, influential authors, and prominent journals in the field, shedding light on the evolving relationship between technology and the economy. The paper might highlight a gap in research on how AI is being adopted and leveraged in developing economies. The actual research gaps addressed in the paper will depend on the findings of their systematic literature review and bibliometric analysis. The significance of this paper reflects a recognition that AI has become a driving force behind innovation, productivity improvements, and competitive advantage across industries. The main objective of this research is to use bibliometric analysis to investigate the publication output about artificial intelligence, using data sourced from the Scopus database, to contribute to economic improvement. The data has been gathered using specified terms, including "artificial intelligence, technologies," and "economy," with a focus on the fields of business management, accounting, and computer sciences. The bibliometric analysis included the use of Scopus to gather data, using VOSviewer, Rstudio, and Excel as analytical tools. The data collection spanned from 2016 to 2023. The primary aims of this work are doing a comprehensive bibliometric analysis, examining the co-citation structure, analyzing keyword co-occurrence, and conducting a geographical analysis within the domain of artificial intelligence and economics. The research yields findings about the implications of publishing in the field of artificial intelligence and its impact on business, management, accounting, and computer science from an academic standpoint. This article aims to assist scholars and business experts seeking to construct contemporary company structures, serving as a valuable resource for future endeavors in this field.